Perfluorooctanoic acid disrupts hepatic metabolism in the developing chicken embryo - Scherbak, Nikolai; Duberg, Daniel; Kråkström, Matilda; Tikka, Pauli; Dickens, Alex M.; Engwall, Magnus; Orešič, Matej; Hyötyläinen, Tuulia (Springer New York LLC, 2026)
Introduction
Perfluorooctanoic acid (PFOA) is a widespread environmental contaminant that interferes with multiple biological pathways, with lipid metabolism being particularly vulnerable. Early-life exposure may disrupt hepatic function during development, but the underlying mechanisms are not fully understood.
Objectives
This study investigated how in ovo exposure to PFOA affects hepatic metabolism in the developing chicken embryo, with a focus on identifying altered metabolic pathways and potential mediators of toxicity.
Methods
Fertilized chicken eggs (Gallus gallus domesticus) were exposed in ovo to six concentrations of PFOA (0–5 µg/g egg). Embryonic liver tissues were analysed by comprehensive metabolomic profiling using two complementary ultra-high-performance liquid chromatography–quadrupole time-of-flight mass spectrometry (UHPLC-QTOF-MS) platforms.
Results
We identified 499 metabolites, including lipids, bile acids, carboxylic acids, amino acids, and phenolic compounds. PFOA exposure caused dose-dependent disturbances in lipid, bile acid, and amino acid metabolism. Notably, multiple secondary bile acids were detected and found to be strongly affected by PFOA, suggesting a central role of bile acid modulation in mediating its effects.
Conclusions
In ovo exposure to PFOA disrupts hepatic metabolism in developing chicken embryos, particularly through alterations in bile acid, lipid, and amino acid pathways. These metabolic changes may impair energy production, endocrine regulation, and organ development, with possible long-term health consequences.